EBUS-guided mediastinal lung cancer staging: monitoring of quality standards improves performance. Issue 8 (4th May 2016) - Evison, Matthew; Crosbie, Philip; Martin, Julie; Shah, Rajesh; Doran, Helen; Borrill, Zoe; Hoyle, Jennifer; Rana, Durgesh; Bailey, Simon; Booton, Richard
Abstract : This audit examined key performance indices related to endobronchial ultrasound (EBUS)-guided mediastinal lung cancer staging before and after the introduction of defined quality standards, at four independent EBUS centres in one cancer network. Data from 642 procedures were prospectively collected and analysed. The introduction of standards was associated with a significant increase (p<0.001) in sampling of key mediastinal lymph node stations (4R, 4L and 7) and a reduction in the variability of staging sensitivity between centres. These data reinforce the requirement for an appropriate regulatory framework for EBUS-transbronchial needle aspiration provision that includes quality assurance and performance monitoring.